O impacto do Simples Nacional na arrecadação do ISS nos municípios cearenses - Pinheiro, Francisca Maria Nóbrega (2023)
The research aims to investigate the impact on the collection of the ISS in the municipalities of Ceará in the presence of the Simples Nacional Law, aimed at analyzing if the municipalities were better in improving the collection of the ISS through the Simples Nacional. The database used in this study was extracted from the portal of the Receita Federal and the Tribunal de Contas dos Municípios - TCM. To do so the econometric model was used with information from 2008 to 2011. The model results show that the Simples Nacional favored an increase in the revenue increment ISS municipalities. Information analysis has also shown a trend of stronger growth in cities with greater economic development.